Challenges Of Mothers Regarding The Autistic Traits Of Their Children - Hazlina Abdullah; Dini Farhana Baharudin; Rahimah Saimin; Nursyuhada’ Ab. Wahab; Myra Aidrin Mohd Ali; Norhana Abdullah; Zarina Ashikin Zakaria (Penerbit USIM, Universiti Sains Islam Malaysia, 2024)
International Language and Education Conference 2021 (iLEC’21) e-PROCEEDINGS “Language and Education : New Norms” 2nd & 3rd November 2021 Organized by : Faculty of Major Language Studies (FPBU), USIM Editor: Azalia Zaharuddin, Suhaili A. Jalil, Kirembwe Rashid Abdul Hameed, Wan Azura Wan Ahmad.